The Susceptibility to Antibiotics of Isolated Bacteria and the Suitability of Antibiotic Regimens to Drugs Susceptibility Test for Patients with Community-acquired Pneumonia at National Hospital 74 - Trung, Tran Thanh; Linh, Vu Khanh; Nhat, Bui Son; Thi Luyen, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3DO - 10.25073/2588-1132/vnumps.4410, 2022)
Abstract: Community-acquired pneumonia (CAP) is a common infectious disease in clinical practice. The objective of the study was to describe the susceptibility to antibiotics of isolated bacteria and to analyze the suitability of antibiotics regimens for treatment after having a drugs susceptibility test (DST) to bacteria in CAP patients. A retrospective study was conducted at National Hospital 74, after screening the medical records of CAP patients hospitalized in the first 6 months of 2021, 32 patients with isolated pathogenic bacteria were included in the study. The results revealed that the percentage of CAP patients who isolated pathogenic bacteria was low. There were 9 isolations of isolated bacteria, in addition to the common bacteria in CAP, also including isolations of bacteria that commonly cause hospital-acquired pneumonia such as P. aeruginosa and S. aureus. Different strains were tested with different antibiotics and had different antibiotic susceptibility despite the same isolations of bacteria. Some physicians have not noticed the role of DST results in the choice of antibiotics for treatment, such as treatment regimens are not suitable for the results of DST, accounting for a high percentage. Keywords: Community-acquired pneumonia, drugs susceptibility test.